İnsan hakları avrupa mahkemesi kararlarında lgbt+ - Sav, Özgür (My University, 2024)
Bu alışmasında, Türkiye’de birçok açıdan tabu olarak değerlendirilen LGBT+ bireyler ve bu bireylerin sahip oldukları haklar ele alınmıştır. Üç bölümden oluşan bu çalışmada, sırasıyla, “LGBT+ Bireylere Yapılan İşkence ve Kötü Muamele ile Ayrımcılık”, “LGBT+ Bireylerin Özel Yaşama Saygı Hakkı Haklarının Korunması” ve “LGBT+ Bireylerin İfade, Toplanma ve Örgütlenme Özgürlükleri” başlıklı bölümlerde Türkiye Cumhuriyeti’nin de taraf olduğu İnsan Hakları Avrupa Sözleşmesi sistematiğine uygun olarak, işkence yasağı, özel ve aile yaşamına saygı, ifade özgürlüğü, toplanma ve örgütlenme özgürlüğü ve ayrımcılık yasağı ile ilgili İnsan Hakları Avrupa Mahkemesi’nin ve Anayasa Mahkemesi’nin LGBT+ bireyler hakkında verdiği kararlar incelenmiştir

This master's thesis study examines LGBT+ individuals, who are considered taboo in many ways in Turkey, and the rights of these individuals. In this three-part study, the decisions of the European Court of Human Rights and the Constitutional Court regarding LGBT+ individuals regarding the prohibition of torture, respect for private and family life, freedom of expression, freedom of assembly and association, and the prohibition of discrimination, in accordance with the systematics of the European Convention on Human Rights, to which the Republic of Turkey is also a party, are examined in the sections titled “Torture and Ill-Treatment and Discrimination Against LGBT+ Individuals”, “Protection of the Rights of LGBT+ Individuals to Respect for Private Life” and “Freedoms of Expression, Assembly and Association of LGBT+ Individuals”.
Keywords: ANAYASA; ANAYASA MAHKEMESİ; Avrupa İnsan Hakları Mahkemesi; Cinsel azınlıklar; CONSTITUTION; CONSTITUTIONAL COURT; Eşcinseller; EUROPEAN CONVENTION ON HUMAN RIGHTS; European Court of Human Rights; Gays; Hukuki durum, kanunlar, vb; İNSAN HAKLARI AVRUPA MAHKEMESİ; İNSAN HAKLARI AVRUPA SÖZLEŞMESİ; Legal status, laws, etc; LGBT+; LGBT+ EUROPEAN COURT OF HUMAN RIGHTS; Sexual minorities; Turkey; Türkiye